Buganda Government Archives - Buganda Government
This includes records on Ministries of Buganda from the time when it was the ruling government to the time when it handed over to the Prote ctorate government 1831-1977, records on Kabaka Yekka one of the partie s in Buganda government 1944-1965, general records on Buganda governmen t for example correspondence relating to government official functions, administration by the katikiro of Buganda, reports on Buganda governme nt buildings 1939-1943, etc and Personalities for example Yusuf Bamuta, Kabali Ezera, Sir Apollo Kagwa, James Miti Kibuka Kabazi, S.K. Masembe Kabali, Hamu Mukasa and Mulira E.
AR/BUG
English and Luganda unless otherwise specified.
Shelf no.1
Keywords: Buganda Government -- Records